New Method for Estimation Mebeverine Hydrochloride Drugs Preparation by a New Analyser: Ayah 6S.X1(WSLEDs)-T.- Two Solar Cells Complied with C.F.I.A (Baghdad Science Journal, 2021)
A sensitivity-turbidimetric method at (0-180o) was used for detn. of mebeverine in drugs by two solar cell and six source with C.F.I.A... The method was based on the formation of ion pair for the pinkish banana color precipitate by the reaction of Mebeverine hydrochloride with Phosphotungstic acid. Turbidity was measured via the reflection of incident light that collides on the surface particles of precipitated at 0-180o. All variables were optimized. The linearity ranged of Mebeverine hydrochloride was 0.05-12.5mmol.L-1, the L.D. (S/N= 3) (3SB) was 521.92 ng/sample depending on dilution for the minimum concentration, with correlation coefficient r = 0.9966while was R.S.D% < 1% of 2, 6 mmol.L-1 conc. of Mebeverine hydrochloride. The method is used successfully for three different of target drugs in three different pharmaceutical formulations. A comparison using t-test was studied. It was shown that there is no significant difference between two values.